Conformable on-skin supercapacitor-integrated, strain sensor based on multioxidant-functionalized thermoplastic polyurethane/reduced graphene oxide/polypyrrole composite films. (13th May 2022) - Park, Daedong; Selvam, Samayanan; Yim, Jin-Heong
Abstract : A hybrid system comprising a conformable on-skin supercapacitor-integrated and strain sensor was developed and found to perform well as a supercapacitor and sensor, with good biocompatibility. This system will be suitable for skin-wearable smart electronic devices. Abstract : A hybrid system comprising a skin-conformal wearable supercapacitor (SC) and a strain sensor was developed. The system is based on thermoplastic polyurethane/reduced graphene oxide/polypyrrole films, surface-treated with iron(iii )–(4-ethylbenzenesulfonic acid), and was found to perform well as a supercapacitor and sensor, with good biocompatibility. This device retains ∼99% of its initial capacity after 5000 cycles. This system will be suitable for skin-wearable smart electronic devices.